Production of Medium-Chain-Length Poly (3-Hydroxyalkanoates) from Saponified Palm Kernel Oil by Pseudomonas putida: Kinetics of Batch and Fed-Batch Fermentations - Annuar, M.S.M.; Tan, I.K.P.; Ibrahim, S.; Ramachandran, K.B. (2006)
The kinetics of medium-chain-length poly(3-hydroxyalkanoates), PHAMCL production by Pseudomonas putida PGA1 in batch and fed-batch fermentations were studied. With saponified palm kernel oil (SPKO) supplying the free fatty acids mixture as the sole carbon and energy source, PHAMCL accumulation is encouraged under ammonium-limited condition, which is a nitrogen stress environment. The amount of PHAMCL accumulated and its specific production rate, qPHA were influenced by the residual ammonium concentration level in the culture medium. It was observed that in both fermentation modes, when the residual ammonium was exhausted (< 0.05 gL-1), the PHAMCL accumulation (11.9) and qPHA (0.0062 h-1) were significantly reduced. However, this effect can be reversed by feeding low amount of ammonium to the culture, resulting in significantly improved PHAMCL yield (71.4) and specific productivity (0.6 h-1). It is concluded that the feeding of low ammonium concentration to the culture medium during the PHAMCL accumulation has a positive effect on sustaining the PHAMCL biosynthetic capability of the organism. It was also found that increasing SPKO concentration in the medium significantly reduced (up to 50) the volumetric oxygen transfer coefficient (KLa) of the fermentation system.